ANALISIS YURIDIS TERHADAP PEMBINAAN NARAPIDANA WANITA BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN (Studi Putusan Nomor 222/Pid.B/2013/PN-Gst) - Asniar Karolina Sarumaha (Jurnal Panah Hukum, 2022)
Imprisonment is one of the penalties contained in the criminal law system in Indonesia. Penitentiary as part of the criminal justice system aims to realize one of the goals of the criminal justice system, namely rehabilitating lawbreakers. Based on this description, the authors are interested in studying and conducting research with the title Thesis of juridical analysis of the development of female prisoners based on Law No. 12 of 1995 concerning Corrections (Decision Study No. 222/Pid.B/2013/PN-Gst). The problem that will be discussed in this research is how to develop female prisoners in prisons. This study aims to determine and analyze the Guidance of Women Convicts in Correctional Institutions. In conducting the research the author uses normative research with the case method. The data used were obtained from library materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. Where the data obtained were analyzed qualitatively. Based on the research findings and discussion, it can be concluded that the juridical analysis of the development of female prisoners based on Law No. 12 of 1995 concerning Corrections (Decision Study No. 222/pid.B/2013/PN.Gst) prisoner development is a program owned by correctional institutions. which is functioned to prepare correctional inmates so that they can interact again with the community properly after the completion of their criminal period. Based on the conclusions above, the authors suggest that the rehabilitation of women convicted of narcotics cases should be carried out